2023
DOI: 10.1039/d3nr00204g
|View full text |Cite
|
Sign up to set email alerts
|

Weakly aligned Ti3C2TxMXene liquid crystals: measuring residual dipolar coupling in multiple co-solvent systems

Abstract: Residual Dipolar Couplings (RDCs), acquired relying on weakly alignment media, are highly valuable for the structural elucidation of organic molecules. Arising from the striking features of no background signal and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…To quantitatively measure the difference in the orientation of artemether in these different media, β angle, an NMR parameter that can be exploited to evaluate the orientation difference in the alignment tensors of a certain solute in two different media systems and quantify the enantiodiscriminating property of a certain alignment medium to enantiomers, , was introduced here. In general, a β angle of 0° means the same orientation of a targeted analyte in two kinds of media, whereas a β angle of 90° suggests orthogonal alignment tensors caused by two different media.…”
Section: Resultsmentioning
confidence: 99%
“…To quantitatively measure the difference in the orientation of artemether in these different media, β angle, an NMR parameter that can be exploited to evaluate the orientation difference in the alignment tensors of a certain solute in two different media systems and quantify the enantiodiscriminating property of a certain alignment medium to enantiomers, , was introduced here. In general, a β angle of 0° means the same orientation of a targeted analyte in two kinds of media, whereas a β angle of 90° suggests orthogonal alignment tensors caused by two different media.…”
Section: Resultsmentioning
confidence: 99%
“…Their study highlighted the influence of the aspect ratio of MXene flakes on the formation of these types of phases. The self-aligning capability of MXene-based dispersions in the presence of socalled co-solvents (CH 3 OH-H 2 O, DMSO-H 2 O, DMF-H 2 O, and acetone-H 2 O) has also been studied in-depth and reported previously [6]. Utilization of MXenes for the development of LC phases has also been successfully reported previously by Usman et al [7] who demonstrated the importance of adding cellulose nanocrystals in MXene-based dispersions for facilitating the formation of various LC phases.…”
Section: Introductionmentioning
confidence: 83%
“…D 2 O-bearing Ti 3 C 2 T x LC medium was obtained from the lyophilized Ti 3 C 2 T x solid after ultrasound-assisted redispersion in D 2 O (Figure 2H). 25 2I). Moreover, these media actualized the accurate RDC acquisition on aromatic analytes such as Boc-D-tryptophan and estrone that were incompatible with unmodified GO media.…”
Section: Mxene Lcmentioning
confidence: 98%
“…(I) [ 1 H, 13 C]-CLIP-HSQC spectra of (+)-IPC obtained in the isotropic DMSO- d 6 /D 2 O solution (red) and anisotropic Ti 3 C 2 T x LC in DMSO- d 6 /D 2 O (blue). Adapted with permission from ref . Copyright 2023 Royal Society of Chemistry.…”
Section: D Colloidal Llc Mediamentioning
confidence: 99%
See 1 more Smart Citation